Effect of urea super granule on the performance of cabbage in Young Jamuna and Brahmaputra Floodplain Soils of Tangail - Hussain, MJ; Ali, MY; Rahman, MA; Quayyum, MA; Choudury, DA (Bangladesh Journal of Agricultural Research, 2010)
A number of experiments were conducted at the Farming Systems Research and Development (FSRD) site, Palima, Tangail for three consecutive years to evaluate the efficiency of USG application in comparison with prilled urea on the yield and yield attributes of cabbage (cv. Atlas-70). There were five treatments, T1= N195 (recommended N dose for HYG, used as prilled urea), T2= N195 (recommended N dose for HYG, used as USG), T3=N175 (N 10% reduction of recommended N dose as USG), T4= N155 (N 20% reduction of recommended N dose as USG), and T5= N105 (Farmers' N dose used as prilled urea). Treatments Tl-T4 received recommended dose of other nutrients (P56K162S13Mo0.6CD3t) and T5 received P25K90S0Mo0CD51 Yield and yield-contributing characters of cabbage significantly responded to the application of USG. The highest head yield (78.1 t/ha) was obtained with the recommended dose of N as USG, and 10% (77.1 t/ha), and 20% (72.0 t/ha) less than the recommended dose of N as USG also produced higher yield than recommended prilled urea-N. Application of USG was found more efficient than prilled urea and the treatment N195P56K162S13Mo0.6CD3t (recommended N as USG for HYG) was found profitable for cabbage cultivation in terms of yield and the treatment N175P56K162S13Mo0.6CD3t (10% N reduction of recommended N dose as USG) was found profitable in terms of economic returns. Keywords: USG; prilled urea; cabbage. DOI: 10.3329/bjar.v35i2.5889 Bangladesh J. Agril. Res. 35(2) : 267-272, June 2010